STUDY ON PREPARATION OF RICE-WHEAT BREAD USING PREMIX - Mahalingam, P.; Veluppillai, S.; Ekanayake, S. (In The Journal of Agricultural Sciences, vol. 9, no. 1, pp. 31-36, 2014, 2014)
In this study the formulation of rice-wheat bread premixes stored for 3, 4, 6 and 8 weeks were investigated aiming to find out the feasibility of preparing rice-wheat bread using premix (rice flour, wheat flour, yeast and bread improver). The breads produced with premixes (rice-wheat premix bread; RWPB) were compared with wheat bread (WB) and rice-wheat bread (RWB) taking into account physical, nutritional and sensorial parameters. Breads were prepared using a basic formula by straight dough method. Based on the determination of gluten percentage of different combinations of rice-wheat flour mixes, flour mix with 20% rice and 80% wheat was selected to prepare premixes. There were no significant differences (p>0-05) between the physical, nutritional and sensorial qualities of RWB and RWPB while the qualities of RWB and RWPB differed significantly (p<0.05) from the qualities of WB. Moisture content of RWB and RWPM was significantly higher (p<0.05) than that of WB. The total sugar contents of RWB and RWPM were significantly higher (p<0.05) than that of WB while total protein content of RWB and RWPM was significantly lower (p<0.05) than that of WB. Fat content of WB was significantly lower than that of RWB and RWPM. There were no significant differences (p>0.05) in ash and crude fiber content of all types of breads. The specific gravity of WB was higher than that of RWB and RWPM and there were no significant differences in the sensory qualities except crumb colour and crust colour. Even though RWB and RWPM differed in some qualities with WB, they did not differ in qualities among them. Therefore from this study it can be concluded that rice – wheat breads can be prepared using premixes stored up to 8 weeks with the qualities consistent with that of bread prepared using fresh rice-wheat flour mix.
Keywords: Premix; RiceWheat Bread; riRice-Wheat Premix Bread